Oral History Program Interview: Charles M. Newsome - Newsome, Charles M.
CALIFORNIA STATE COLLEGE, BAKERSFIELD CALIFORNIA ODYSSEY The 1930s Migration to the Southern San Joaquin Valley Oral History Program Interview Between INTERVIEWEE: Charles M. Newsome PLACE OF BIRTH: Fort Gibson, Muskogee County, Oklahoma INTERVIEWER: Michael Neely